Structural, morphological, and opto‐electrical properties of Y2‐xYbxO3 nanoparticles synthesized using co‐precipitation method. Issue 1 (10th September 2020) - Kumar, Sushil; Tripathi, Harshit; Sharma, Jagmohan; Batra, Uma
Abstract: Advanced polycrystalline ceramics are gaining importance on development of light‐emitting diodes, infrared detectors, solid‐state lasers, etc. The physical properties of these materials are dependent on variety of dopant concentrations. In this manuscript, we have synthesized Yb‐doped Y2 O3 (Y2‐x Ybx O3 ) (x = 0.0, 0.02, 0.06, 0.1, 0.14) nanoparticles using co‐precipitation method. X‐ray diffraction patterns confirm the presence of cubic phase for pure Y2 O3 nanoparticles and mixed phase (cubic + monoclinic) for Yb‐doped Y2 O3 nanoparticles. The average crystallite size is found in the range 71 to 31 nm and lattice strain −1 × 10 −4 to‐5 × 10 −4 calculated using Debye‐Scherrer formula and Willimission‐Hall plot. The crystallite size decrease with dopant concentration upto x = 0.10 and material is found to exhibit compressive lattice strain. Field‐emission scanning electron microscopy shows agglomerated nanoparticles. The Fourier‐transform infrared spectroscopy confirms the presence of metal oxide functional groups (Y‐O and Yb‐O) and vibrational bands corresponding to O‐H vibration, C‐O bending, and stretching modes in the samples. The band gap energy ( E g ) is found to decrease from 5.14 eV for x = 0.0 to 3.60 eV for x = 0.14 composition. The photolumincence spectra show characteristic blue and green emission at 486 nm for x = 0.10 and 525 nm for x = 0.0, respectively. The frequency‐dependent dielectric studies confirm the enhancement in dielectric constant with increase in Yb doping. These structural, morphological, optical, and electrical properties of Yb:Y2 O3 nanoparticles are helpful for selecting this material as an appropriate candidate for laser host material for medical imaging and display devices applications.